Self- efficacy and resilience among late adolescent - Nor Syakila Jaeh; Amalia Madihie (Journal of Counseling and Educational Technology, 2019)
The aim of this study is to examine the relationship between self- efficacy and resilience among late adolescents in the five components of resilience which are meaningfulness, perseverance, self- reliance, equanimity and existential aloneness. The number of sample was 250, aged between 18-19 year olds.  Generalized Self- Efficacy (GSE) by Schwarzer and Jerusalem (1995) and Resilience Scale (RS) by Wagnild and Young (1993) were carried out. Results showed that there are significant relationships between self- efficacy and resilience in the form of meaningfulness, perseverance, self- reliance, equanimity and existential aloneness where the null hypothesis is being rejected. These findings can be used to design effective intervention to solve the client issue related with self- efficacy and resilience and promote positive behaviour such as resilience. Future research could conduct research for early adolescent, middle adolescent and late adolescent which can lead to new contribution to the research.